2016
DOI: 10.1038/cddis.2016.172
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the scaffold WD40 protein WRAP53β enhances the repair of and cell survival from DNA double-strand breaks

Abstract: Altered expression of the multifunctional protein WRAP53β (WD40 encoding RNA Antisense to p53), which targets repair factors to DNA double-strand breaks and factors involved in telomere elongation to Cajal bodies, is linked to carcinogenesis. While loss of WRAP53β function has been shown to disrupt processes regulated by this protein, the consequences of its overexpression remain unclear. Here we demonstrate that overexpression of WRAP53β disrupts the formation of and impairs the localization of coilin to Caja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…WRAP53β has recently been shown to be a rate-limiting factor in the repair of double-strand breaks and overexpression of this protein results in more efficient HR and NHEJ repair and fewer DNA breaks 15 . Therefore, we asked whether phosphorylation of WRAP53β influences HR and NHEJ employing reporter assays that measure restoration of a functional GFP protein by these processes.…”
Section: Resultsmentioning
confidence: 99%
“…WRAP53β has recently been shown to be a rate-limiting factor in the repair of double-strand breaks and overexpression of this protein results in more efficient HR and NHEJ repair and fewer DNA breaks 15 . Therefore, we asked whether phosphorylation of WRAP53β influences HR and NHEJ employing reporter assays that measure restoration of a functional GFP protein by these processes.…”
Section: Resultsmentioning
confidence: 99%
“…The inability of mutant WRAP53β to accumulate in Cajal bodies and/or bind known interaction partners prevented various functions of this protein at this site. First, high overexpression of the mutant forms did not result in the collapse of Cajal bodies and/or inability of this organelle to form, in contrast to high overexpression of the wild-type protein 26,32 . Second, the mutant proteins no longer interacted with SMN, coilin, scaRNAs or telomerase, interactions known to be required for the localization of these factors to Cajal bodies [24][25][26] .…”
Section: Discussionmentioning
confidence: 94%
“…Proper assembly of WRAP53β in Cajal bodies is essential for their maintenance, as demonstrated by the findings that either loss or overexpression of WRAP53β causes these organelles to collapse, after which they cannot re-form 24,26,31,32 . Accordingly, overexpression of exogenous wild-type WRAP53β here led to the disappearance and/or prevented the formation of Cajal bodies in approximately half of the cells transfected ( Fig.…”
Section: Mutations In Wrap53β Impair Its Localization To the Nucleus mentioning
confidence: 99%
“…It was reported that TCAB1 RNAi in U2OS, H1299 and HeLa cells increased the number of phospho-histone H2AX (γ-H2AX) foci in nonirradiated cells, indicating TCAB1 protects cells against accumulation of spontaneous DNA damage [14]. Cells overexpressing TCAB1 exhibited more rapid clearance of γ-H2AX, in association with homologous recombination and non-homologous end-joining at sites of less DNA breaks [26]. Reduced expression of TCAB1 in ovarian tumors correlated with attenuated DNA damage response and poor patient survival [19].…”
Section: Discussionmentioning
confidence: 99%